Creative Contamination - The Editors (University of Oklahoma Libraries, 2021)
Jack Zipes conceptualizes the process of adaptation as contamination, a term used by folklorists to describe foreign augmentation to what appears to be a pure narrative tradition. Although this has traditionally had a negative connotation, Zipes (2001) posits that it has generative aspects as well. "Contamination can be an enrichment process; it can lead to the birth of something unique and genuine in its own right" (p.102). We see the process of contamination at work in adaptations.